PENERAPAN PRINSIP-PRINSIP HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) DALAM PENYELENGGARAAN MAKANAN LAUK HEWANI DI INSTALASI GIZI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Annisya Fauzia; Friska citra Agustia (Jurnal Gizi dan Pangan Soedirman, 2018)
Background : Animal foodstuffs are the main source of bacteria which cause infection and intoxication; also they are susceptible to undergo contamination either by physical, biological, and chemical hazards. HACCP system is the only one quality assurance system with food safety-based that becomes food reference in the world. This system also becomes the standardization of food safety system in hospital. RSUD Prof. Dr. Margono Soekarjo Purwokerto which is the referral hospital for Provincial Level has implemented HACCP system as safety system in food service. The purpose of this research is to know implementation of HACCP priciples on animal side dishes food process in nutritional installation of RSUD Prof. Dr. Margono Soekarjo Purwokerto. Methodology : This research uses observational qualitative approach with descriptive method. The data collection is conducted through semi-structured interview, observation of moderate participation and document analysis. The informants are chosen by using purposive sampling which is based on inclusion and exclusion criteria. Observation is conducted toward the processing of 4 kinds of animal side dishes. The data obtained are analyzed by reducing the data, displaying the data and drawing the conclusion. Research Result : The risk identification in the processing of animal side dishes is conducted toward microbiological, chemical and physical hazards. The determination of CCP is done by using Codex Decission Tree. The determination of critical limit for each CCP is performed by arranging stages which include CCP then compiling parameters and critical limit of each parameter. The system verification is done by monitoring the final products regularly and conducting laboratory test on the final products. The corrective action is arranged based on the risk level. The recording and documentation of HACCP have not covered all kinds of animal side dishes on ten-day cycle menu in Nutritional Installation of RSUD Prof. Dr. Margono Soekarjo. Conclusion : The implemetation of HACCP system as food service security system in Nutritional Installation of RSUD Prof. Dr. Margono Soekarjo refers to the principles of HACCP.